Inactivation of γ‐secretases leads to accumulation of substrates and non‐Alzheimer neurodegeneration - Acx, Hermien; Müller, Ulrike C. (EMBO molecular medicine, 2017)
γ‐Secretases are a family of intramembrane cleaving aspartyl proteases and important drug targets in Alzheimer's disease. Here, we generated mice deficient for all γ‐secretases in the pyramidal neurons of the postnatal forebrain by deleting the three anterior pharynx defective 1 (Aph1) subunits (Aph1abc cKO Cre+). The mice show progressive cortical atrophy, neuronal loss, and gliosis. Interestingly, this is associated with more than 10‐fold accumulation of membrane‐bound fragments of App, Aplp1, Nrg1, and Dcc, while other known substrates of γ‐secretase such as Aplp2, Lrp1, and Sdc3 accumulate to lesser extents. Despite numerous reports linking neurodegeneration to accumulation of membrane‐bound App fragments, deletion of App expression in the combined Aph1 knockout does not rescue this phenotype. Importantly, knockout of only Aph1a‐ or Aph1bc‐secretases causes limited and differential accumulation of substrates. This was not associated with neurodegeneration. Further development of selective Aph1‐γ‐secretase inhibitors should be considered for treatment of Alzheimer's disease. Synopsis γ‐Secretases are proteases with central roles in Alzheimer's disease pathogenesis. The impact of partial and combined deficiencies of the Aph1‐γ‐secretase subunits on mouse brain was investigated at biochemical and morphological levels with a focus on potential neurodegenerative phenotypes. Combined Aph1abc‐γ‐secretase cKO (conditional knock out) animals suffer from progressive neurodegeneration.Neurodegeneration, characterized by strong accumulation of APP‐carboxyterminal fragments, is not modulated by decreased expression of APP.Accumulation of APP and other substrates is much less outspoken in single Aph1a or Aph1bc knockout mice and these mice do not display neurodegeneration.Aph1bc targeted animals display a significant effect on Aβ42 generationThe in vivo substrate selectivity of two different γ‐secretase subtypes is demonstrated.